Modelos cognitivos na categorização de "violência" : estruturas e processos no discurso de sujeitos urbanos, rurais e "rurbanos" - Säge, Morgana Larissa (My University, 2014)
The guiding problem of this dissertation is: how do urban, rural and rurban individuals of the region of Caxias do Sul structure the category VIOLENCE, on the basis of cognitive models, which emerge from the way these individuals express linguistically their experiences in this domain? The general objective is to investigate, in the field of Cognitive Linguistics (CL), Cognitive Semantics more specifically, which processes and structures are implied in the categorization of VIOLENCE from the analysis of parts of interviews carried out with urban, rural and rurban individuals of the region of Caxias do Sul. The sample is constituted by 20 interviews, which generates a corpus for analysis. The analyses are founded on the Theory of Idealized Cognitive Models (ICMT) and its theoretical consequences, with emphasis on metaphorical and metonymical models. This investigation is particularly relevant since VIOLENCE is a complex abstract concept, whose structuring is strongly connected to cognitive and sociocultural factors. The general objective is opened up in the following specific objectives: (a) to identify and analyze the structure of the category VIOLENCE in terms of metaphorical and metonymical mappings; and (b) to discuss methodological issues concerning the interview, thus evaluating its adequacy as a survey instrument in CL. Hypotheses formulated on the basis of the survey problem are: (1) metaphorical models structuring the category differ in urban, rural and rurban subjects; (2) metonymical models, which are culturally motivated, differ among urban, rural and rurban subjects; (3) the individual interview, as initially proposed, constitutes a legitimate speech act for analysis in CL as long as a set of technical-procedural requirements is met. After analyzing the corpus, it has been noticed that hypotheses (1) and (2) are not confirmed completely because, although the sample presents rich metaphorical and metonymical mappings, these do not differ due to the criterion of belonging to a certain community but rather due to schooling. However, the verification of these hypotheses should deserve further attention in later surveys, and with a larger sample size. Hypothesis (3) was confirmed, once the discourses generated in this type of speech event supplied highly relevant data to investigate the structuring of the category VIOLENCE, which can be still explored in new surveys focusing on more specific aspects of certain linguistic manifestations.
O problema norteador desta dissertação é: como indivíduos urbanos, rurais e rurbanos, da região de Caxias do Sul, estruturam a categoria VIOLÊNCIA, a partir de modelos cognitivos, os quais emergem do modo como esses indivíduos expressam linguisticamente suas experiências nesse domínio? O objetivo geral é o de investigar, no âmbito da Linguística Cognitiva (LC), especificamente da Semântica Cognitiva, quais processos e estruturas estão implicados na categorização de VIOLÊNCIA, a partir da análise de trechos de entrevistas realizadas com indivíduos urbanos, rurais e rurbanos da região de Caxias do Sul. A amostra é constituída de 20 entrevistas, a partir das quais é gerado o corpus para análise. As análises fundamentam-se na Teoria dos Modelos Cognitivos Idealizados (TMCI) e seus desdobramentos teóricos, com ênfase em modelos metafóricos e metonímicos. Esta investigação é particularmente relevante à medida que VIOLÊNCIA é um conceito abstrato complexo, cuja estruturação se encontra fortemente ligada a fatores cognitivos e socioculturais. O objetivo geral desdobra-se nos seguintes objetivos específicos: (a) identificar e analisar a estrutura da categoria VIOLÊNCIA em termos de mapeamentos metafóricos e metonímicos; e (b) discutir questões metodológicas atinentes à entrevista, avaliando sua adequação como o instrumento da pesquisa em LC. As hipóteses formuladas a partir do problema de pesquisa são: (1) modelos metafóricos, que estruturam a categoria, diferem entre sujeitos urbanos, rurais e rurbanos; (2) modelos metonímicos, que são culturalmente motivados, diferem entre sujeitos urbanos, rurais e rurbanos; (3) a entrevista individual, como inicialmente proposta, constitui-se como um ato de fala legítimo para análise em LC, à medida que um conjunto de requisitos técnico-procedimentais for atendido. A partir da análise do corpus, verifica-se que as hipóteses (1) e (2) não se confirmam completamente, uma vez que, apesar de se observarem, na amostra, ricos mapeamentos metafóricos e metonímicos, com maior ocorrência de modelos metonímicos, estes não diferem em função do critério de pertencimento a dada comunidade, mas sim em função da formação escolar. Entretanto, a verificação dessas hipóteses deve ainda merecer atenção em pesquisas posteriores com ampliação dessa amostra. A hipótese (3) é confirmada, à medida que os discursos gerados nesse tipo de evento de fala forneceram dados altamente relevantes para a investigação da estruturação da categoria VIOLÊNCIA, os quais podem ainda ser explorados em novas pesquisas que focalizem aspectos mais específicos de determinadas manifestações linguísticas.
Keywords: Linguistica; Semântica cognitiva; Categoria violência; Modelos metafóricos e modelos metonímicos; Entrevista; Gramática cognitiva; Língua portuguesa - Figuras de linguagem; Cognição; Linguagem e línguas - Estudo de casos; Cognitive semantic; Category violence; Metaphorical models and metonymical models; Interview; Cognitive grammar; Portuguese language - Figures of speech; Cognition; Language and languages - Case studies